Cactus Bug, Chelinidea vittiger aequoris McAtee (Insecta: Hemiptera: Coreidae) - Frank W. Mead; J. R. Herring (EDIS)
Insects that attack prickly pear cacti, Opuntia spp., in North America have been under investigation for a century. The primary purpose of this research has been to determine which insects have the most promise as biocontrol agents where cacti are severe weed problems. In Australia, for example, over 30,000,000 acres of pasture land were rendered useless because of dense stands of exotic prickly pear cacti. One of the native American cactus insects that showed early promise as a control agent was the coreid bug, Chelinidea vittiger Uhler. DeVol and Goeden (1973) discussed the value of this species in biological weed control and reported that it was ineffective in controlling prickly pears in Australia and Santa Cruz Island, California. In most areas of North America prickly pears are not a problem because a complex of insects keeps them under control. Chelinidea vittiger is considered a minor component of that complex. In Florida and the other southeastern states, the only Chelinidea present is C. vittiger aequoris McAtee. This document is EENY-208 (originally published as DPI Entomology Circular 149), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2001. Revised: August 2003.